2018
DOI: 10.1556/066.2018.47.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Rehydration of osmotically pre-treated apple cubes dried by hot air, microwave, and freeze-drying

Abstract: Effects of the osmotic pre-treatment (OD) with sucrose or sorbitol solutions and different drying methods on the rehydration kinetics of apple cubes were studied. Samples were dried by hot air (HAD) at 70 ºC, by microwave (MWD) at 500 W, and by freeze-drying (FD). The rehydration of dried samples was performed in water at 80 ºC and at a mass ratio of sample to water of 1:100. The fi rst order kinetic model was found to provide the best fi t of the rehydration data. The pre-treatment and the drying method did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…When the hot air temperature was 70°C, the chewiness reached its lowest value of 2,495.28 g. These results showed that the purple cabbage dried at 50 ~ 70°C had a better drying quality than the other treatments. This was due to the moisture evaporation on the materials surface was slow at low hot air temperature, and the enzymatic browning reaction catalyzed by polyphenol oxidase (Assis et al., 2018 ; Wang, Liu, et al., 2019 ). When the hot air temperature increased, the antioxidant substances in the cabbages, including anthocyanin, polyphenols, and flavonoids, caused severe heat damages and intensified the Maillard reaction (Xia, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When the hot air temperature was 70°C, the chewiness reached its lowest value of 2,495.28 g. These results showed that the purple cabbage dried at 50 ~ 70°C had a better drying quality than the other treatments. This was due to the moisture evaporation on the materials surface was slow at low hot air temperature, and the enzymatic browning reaction catalyzed by polyphenol oxidase (Assis et al., 2018 ; Wang, Liu, et al., 2019 ). When the hot air temperature increased, the antioxidant substances in the cabbages, including anthocyanin, polyphenols, and flavonoids, caused severe heat damages and intensified the Maillard reaction (Xia, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Because the weighing took only a few seconds, it had little effect on the drying process (Wang et al., 2019 ; Yu et al., 2020 ). The cabbage slices were dried in 101‐2AB blast drying box at various temperatures (40, 50, 60, 70, or 80°C), with recirculation of air with 10%‐20% relative humidity and at approximately 1 m/s (Assis et al., 2018 ; Wang, Li, et al., 2019 ). The cabbage slices were also dried with a microwave density of 2.75 W/g reached the conversion point (30%, 40%, 50%, 60%, or 70%), and the microwave drying was replaced by hot air drying at 60°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The schematic representation of the system was presented in Figure 1. During hot air drying, T. albuminosus were dried at a wind speed of 0.5 m/s and a relative humidity of 15%-30% (Assis et al, 2018;, until the moisture content was 12%. The dried products were in accord with national standard requirements for edible fungi and their products in GB 7096-2014.…”
Section: Processmentioning
confidence: 99%
“…They optimized drying temperature, air velocities, and loading densities, and drying times for hot air drying using response surface method. Assis et al [16] studied the effects of the osmotic pre-treatment with sucrose or sorbitol solutions and different drying methods on the rehydration kinetics of apple cubes. Samples were dried by hot air at 70 • C, by microwave at 500 W, and by freeze-drying.…”
Section: Introductionmentioning
confidence: 99%